Impact of the Supply Chain on Sustainable and Business Performance During the COVID-19 Pandemic - Pinzón Castro, Sandra Yesenia; Maldonado Guzman, Gonzalo (Mercados y Negocios, 2024)
The main objective of this empirical study is to provide empirical evidence that allows quantifying the impact of the supply chain on sustainable and firm performance during the COVID-19 pandemic. An electronic survey was applied to collect information on 65 manufacturing firms selected through simple random sampling, using the statistical technique of Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze the data obtained using the SmartPLS 4.0 software. Furthermore, the analysis carried out in this study identifies a need for more theoretical and, above all, empirical evidence in this area, which prevents the generalization of the results obtained. Likewise, the results suggest that during the COVID-19 pandemic, the supply chain positively impacted sustainable performance. However, an adverse effect was also detected on firm performance, so it is possible to conclude that the COVID-10 pandemic substantially improved the sustainable performance of manufacturing companies. However, it also generated a decrease in their level of firm performance.